Analisis Portofolio Optimal Saham Syariah Jakarta Islamic Index (JII) Periode 2015-2017 - Derry Permata; Rindah F Suryawati (IPB University, 2020)
Trend of stock investment in Sharia Stock Market has been rising from 2015-2017. This trend must be followed by a comprehensive understanding of investors in choosing a profitable stock combination by considering a measurable risk and rates of return. This research aims to identify optimal sharia portfolio theory of Markowitz Model with the lowest preference risk, Markowitz Model with optimal sharpe ratio, and Single Index Model. The analysis then aims to compare expected return and portfolio risk levels formed from the three models, and to provide optimal portfolio recommendations to investors that can be used as consideration of decision making in investing in sharia Jakarta Islamic Index. This research uses reports of daily stock price, dividend, IHSG, and sukuk. The eighteen object in this research were obtained from a purposive sampling method. Based on the calculation, optimal portfolio was obtained using Markowitz model with optimal Sharpe ratio which resulted in the best combination of stock with expected rate of return and risk level of 33,74 percent and 22 percent in a year.